Concepções de meio ambiente de professores de educação básica e práticas pedagógicas em educação ambiental - Kus, Helder Jaime (2012)
This paper reports a survey conducted in two establishments of public high school located in Cleveland in Paraná, whose goal was to identify and analyze the conceptions of the environment of teachers and compare them with their teaching practices in environmental education. The study twenty-four teachers. There were representatives from all disciplines of the regular high school, of which twenty-one were female and three male. The age range was between 21 and 48 years. Data were collected through a questionnaire composed of 10 questions, with the first seven aimed at identifying the conceptions of education and environmental education and the other aimed at identifying the core of social representations of the environment of the subjects, by use of an inductive term as the usual procedures in research aimed at identifying the core of a social representation. The data were organized and analyzed using the techniques of content analysis techniques and the theory of the core, with the theoretical theory of social representations of Serge Moscovici. The results suggest that the core of the social representation of the environment of the subjects, points to the importance attached to preserving natural resources, especially water and special attention to environmental degradation. Regarding the design of environmental education of the subjects, the results highlight for the sense that this education is conceived and executed as a set of educational practices aimed at the development of attitudes towards the preservation of the environment. Thus, the results showed that there is coherence between what teachers mean by the environment and how they develop and implement its practices in environmental education.